Nanoporous PdCe bimetallic nanocubes with high catalytic activity towards ethanol electro-oxidation and the oxygen reduction reaction in alkaline media. Issue 46 (12th November 2018) - Chen, Jiyun; Li, Yao; Lu, Nali; Tian, Chunhuan; Han, Zhida; Zhang, Lei; Fang, Yong; Qian, Bin; Jiang, Xuefan; Cui, Rongjing
Abstract : In this work, we reported a simple method to fabricate nanoporous PdCe (NP-PdCe) nanocubes with high activity and good stability by melt spinning combined with chemical dealloying. Abstract : In this work, we reported a simple method to fabricate nanoporous PdCe (NP-PdCe) nanocubes with high activity and good stability by melt spinning combined with chemical dealloying. The microstructure results show that the prepared NP-PdCe alloy consists of nanocubes with an average size of 200 nm, exhibiting a three-dimensional nanoporous structure with a pore size of around 5 nm. Owing to the combined effect of bimetallic synergistic action and the nanoporous structure, the NP-PdCe catalyst exhibits much higher electrocatalytic activity and durability towards ethanol electro-oxidation and the oxygen reduction reaction in alkaline solution, relative to nanoporous Pd and commercial Pd/C catalysts. With the advantages of scalable preparation and enhanced catalytic performance, the NP-PdCe nanocubes hold great potential for application as a promising catalyst in direct ethanol fuel cells.